Taxation and Valuation of International Real Investments - Jouko Ylä-Liedenpohja (Center for Economic Studies and ifo Institute (CESifo), 2003)
The study analyses the incentives for multinationals caused by linking different national tax systems. The dividend tax capitalization hypothesis is extended to include taxes during the repatriation and onward distribution (as equalization tax) to derive the relevant cost of capital formulae for each source of finance. No clear tax advantage of using debt from the parent to the foreign subsidiary is found. Tax conditions are derived for finance companies in third countries used by multinationals to park and rotate profits such as realization gains from trade sales of their subsidiaries. The same tools are applied to analyse corporate inversions.
Keywords: 330; multinational taxation; equalization tax; profit valuation